Lyase activity of glycogen synthase: Is an elimination/addition mechanism a possible reaction pathway for retaining glycosyltransferases? - Díaz, Adelaida; Díaz-Lobo, Mireia; Grados, Enrique; Guinovart, Joan J; Fita, Ignacio; Ferrer, Joan C (IUBMB life, 2012)
Despite the biological relevance of glycosyltrasferases (GTs) and the many efforts devoted to this subject, the catalytic mechanism through which a subclass of this large family of enzymes, namely those that operate with net retention of the anomeric configuration, has not been fully established. Here, we show that in the absence of an acceptor, an archetypal retaining GT such as Pyrococcus abyssi glycogen synthase (PaGS) reacts with its glucosyl donor substrate, uridine 5'-diphosphoglucose (UDP-Glc), to produce the scission of the covalent bond between the terminal phosphate oxygen of UDP and the sugar ring. X-ray diffraction analysis of the PaGS/UDP-Glc complex shows no electronic density attributable to the UDP moiety, but establishes the presence in the active site of the enzyme of a glucose-like derivative that lacks the exocyclic oxygen attached to the anomeric carbon. Chemical derivatization followed by gas chromatography/mass spectrometry of the isolated glucose-like species allowed us to identify the molecule found in the catalytic site of PaGS as 1,5-anhydro-D-arabino-hex-1-enitol (AA) or its tautomeric form, 1,5-anhydro-D-fructose. These findings are consistent with a stepwise S(N) i-like mechanism as the modus operandi of retaining GTs, a mechanism that involves the discrete existence of an oxocarbenium intermediate. Even in the absence of a glucosyl acceptor, glycogen synthase (GS) promotes the formation of the cationic intermediate, which, by eliminating the proton of the adjacent C2 carbon atom, yields AA. Alternatively, these observations could be interpreted assuming that AA is a true intermediate in the reaction pathway of GS and that this enzyme operates through an elimination/addition mechanism.